Pengaruh Job Insecurity Terhadap Turnover Intention Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Karyawan Pt. Mitra Madura Dharma Abadi - Unsul Abrar; Syaiful Anwar; Nur Qoudri Wijaya (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2021)
The development of an increasingly advanced era requires every profit organization or company to always compete tightly with several aspects that are owned internally, for example, in the aspect of human resources, they must always adapt to technological developments, so from several phenomena that occur in a company, this research ends. raised various important issues in the company's performance in terms of human resources such as job insecurity in several companies which can have an impact on the performance and turnover intention of the human resources themselves so that there needs to be organizational commitment within the company, of course with some policies and solutions from the company management . This research was conducted by a method in accordance with the observations in the field, including by lifting the intervening variable organizational commitment that can only be used in quantitative research approach path analysis method, data were obtained from filling the questionnaire that has been distributed to the employees in PT. Madura Dharma Abadi Partners. The results of the study concluded that the job insecurity variable can have a direct effect on turnover intention and can also have an indirect effect through the organizational commitment variable with a significant level of 10%, the magnitude of the direct effect is 0.704 while the magnitude of the indirect effect must be calculated by multiplying the indirect coefficient (0.023). ) x (0.089) = 0.002047. Therefore, the results obtained are the direct effect is higher than the indirect effect